Strategi Pembinaan Akhlak Santri di Pondok Pesantren Darussholihat Andong Boyolali - Al Qony Puspasary; Baidi Baidi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to describe the moral values instilled by Ustadzah and the strategies used in shaping the students' character at Darussholihat Islamic Boarding School in Andong Boyolali, as well as to evaluate the results of implementing these strategies. This research uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation. The results of the study indicate that the moral values instilled include honesty, discipline, piety (wara’), responsibility, love for Allah SWT, and acceptance of His decrees. The strategies applied by Ustadzah utilize behavioristic and social constructivist approaches. The behavioristic approach emphasizes reward and punishment, habituation of worship, shaping techniques, and self-reflection. Meanwhile, the social constructivist approach is manifested through peer mentoring, collaborative learning, and discussions on moral values. This strategy has proven effective in shaping students' character to be disciplined, self-aware, and in fostering a learning environment that supports moral development. The intensive role of the Ustadzah as a 24-hour mentor is key to the success of this strategy.